Analisis Kebutuhan Masyarakat terdampak Banjir Rob: Studi Kasus Kota Pekalongan - Kuat Ismanto; Suryo Pratikwo; Benny Diah Madusari; Paminto Agung Christianto (JURNAL LITBANG KOTA PEKALONGAN, 2021)
This paper identifies the needs of victims affected by tidal flooding. In addition, it explores people's expectations of government policies in resolving tidal floods. The research was conducted in Pekalongan City which includes four sub-districts. Data were obtained through observation, questionnaires, interviews, documentation, and Focus Group Discussions (FGD) . From the distribution of questionnaires obtained 100 respondents. The FGD was held by inviting government agencies in Pekalongan City and having involvement in the problem of tidal flooding. The results of the study show that the needs of the community affected by the tidal flood that must be met on a priority basis include: basic food needs, health needs, survival needs, spiritual and (religious) needs. From the results of the F GD, it was concluded that each agency had worked according to its duties. However, coordination and consolidation need to be improved. From this research, priority needs and disaster management strategies can be drawn that can be used for handling Keywords: Pekalongan City; tidal flood, disaster mitigation; refugee needs